Modified magnesium oxysulfate inorganic glue, preparation method thereof and bamboo chip board
By combining modified magnesium sulfhydryl inorganic glue with bamboo chips, the shortcomings of traditional bamboo chip materials in environmental adaptability, adhesion and mechanical properties are solved, and bamboo chip boards with excellent mechanical properties and environmental protection are prepared, suitable for Various application areas.
Patent Information
- Application Number
- CN202510065189.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2045-01-16
AI Technical Summary
Traditional bamboo chip materials have shortcomings in environmental adaptability, adhesion and mechanical properties, and there are problems of formaldehyde release and fire hazards.
Modified magnesium sulfide and magnesium inorganic glue and bamboo chips are used to combine them with bamboo chips, and the addition of modifiers such as citric acid, fume and nanosilicon, as well as stabilizers such as ceramoleite powder and multi-wall carbon nanotubes, increase the between inorganic glue and bamboo chips. adhesion and overall mechanical properties.
The modified sulfhydryl magnesium inorganic rubber bamboo chip boards have excellent mechanical properties, fire resistance, environmental protection and water resistance. They are suitable for construction, furniture and other fields, reducing energy consumption and carbon dioxide emissions.
Smart Images

Figure CN119461913A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid waste treatment, and in particular relates to a modified magnesium oxysulfate inorganic glue and a preparation method thereof and a bamboo chip board. Background Art
[0002] Bamboo is a green and renewable resource. Due to its short growth cycle, high strength and good mechanical properties, it is widely used in construction, furniture, papermaking, textiles and other fields. However, a large amount of waste bamboo chips is generated during bamboo processing, usually accounting for 5%-15% of the total weight of bamboo. If these bamboo chips are not effectively utilized, they are often discarded or burned, resulting in resource waste and environmental pollution.
[0003] Traditional bamboo scraps are mostly processed with organic adhesives such as "trialdehyde glue" (urea-formaldehyde resin, phenolic resin, melamine-formaldehyde resin), but these materials have poor environmental adaptability and have problems such as formaldehyde release, environmental pollution, and fire hazards. Bamboo scraps, as a natural organic fiber, contain hydroxyl groups (-OH) and other hydrophilic functional groups on its surface, which makes its bonding with inorganic glue relatively weak. The structure prepared with bamboo scraps and inorganic glue has poor compressive strength and flexural strength, and poor toughness. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a modified magnesium oxysulfide inorganic glue, a preparation method thereof and a bamboo chip board. By compounding the modified magnesium oxysulfide inorganic glue with waste bamboo chips, an inorganic glue bamboo chip board with excellent mechanical properties, fire resistance, environmental protection performance and water resistance is prepared.
[0005] In order to achieve the above object, the present invention is implemented through the following technical solutions: In a first aspect, the present invention provides a modified magnesium oxysulfide inorganic glue, which is composed of the following components by mass: 100 parts of light-burned magnesium oxide, 20-60 parts of magnesium sulfate heptahydrate, 50-85 parts of water, 1.1-17 parts of a modifier and 1.8-5.3 parts of a stabilizer; The modifier comprises: 0.2-3 parts of citric acid, 0.5-8 parts of silica fume, 0.1-3 parts of silica sol, 0.2-2 parts of lithium silicate, 0.1-1 parts of sodium tripolyphosphate and 0.5-5 parts of nano silicon; The stabilizer comprises: 1-3.5 parts of amphibole powder, 0.5-3 parts of sodium silicate and 0.3-0.8 parts of multi-walled carbon nanotubes.
[0006] The invention mainly uses light-burned magnesium oxide and magnesium sulfate heptahydrate as base materials, generates magnesium oxysulfide inorganic glue after chemical reaction, and has good durability and environmental protection. However, magnesium oxysulfide has the disadvantages of low strength and poor bonding performance, and needs to add a modifier and a stabilizer to improve the bonding force between it and bamboo chips and the overall mechanical properties. In addition, adding light-burned magnesium oxide can further improve the fire resistance of the colloid.
[0007] Among the modifiers, citric acid can slow down the coagulation rate of inorganic glue, improve the hydration process of magnesium oxysulfide inorganic glue, and effectively improve the mechanical properties of the colloid; silica fume can improve the microstructure of the hydration product and improve the compressive strength and toughness of the colloid; silica sol, as a water-soluble silicate colloid, can form a dense three-dimensional network structure in magnesium oxysulfide inorganic glue, enhancing the structural stability of the colloid; lithium silicate can be used as a reactive silicon source in magnesium oxysulfide inorganic glue to enhance the hardness and corrosion resistance of the colloid; sodium tripolyphosphate can improve the fluidity and stability of the colloid, prevent the components from being separated or precipitated, and enhance the overall structure of the colloid, wherein phosphate ions react with the hydroxyl and cellulose on the surface of bamboo chips, promote physical adsorption and chemical bonding between the inorganic glue and bamboo chips, and improve the bonding between the two; nano silicon particles have a high specific surface area and can react strongly with other components (such as magnesium oxide and magnesium sulfate), improve the microstructure of the colloid, form a good interface contact with the surface of bamboo chips, and further improve the bonding performance between the colloid and bamboo chips.
[0008] Among the stabilizers, the layered structure of hornblende powder can improve the mechanical strength of the inorganic glue, while reducing the cracks generated during the hardening process, which helps to improve the stability and durability of the modified inorganic glue. The introduction of hornblende powder can also improve the wettability of the colloid and promote good bonding with bamboo chips; the aqueous solution of sodium silicate, commonly known as water glass, can effectively reduce the dispersibility of the cementitious material in water, improve the waterproof performance of the inorganic glue, and improve the long-term stability of the colloid strength; the surface of multi-walled carbon nanotubes has rich hydrophilic and hydrophobic functional groups, which can improve the compatibility of the colloid with waste bamboo chips, thereby enhancing the bonding ability of the colloid. At the same time, multi-walled carbon nanotubes have excellent thermal stability and thermochemical properties, which can improve the fire resistance and corrosion resistance of magnesium oxysulfide inorganic glue, and can prevent the interface peeling between bamboo chips and inorganic glue caused by environmental factors, thereby improving the durability of inorganic glue bamboo chip board.
[0009] In some embodiments, the modified magnesium oxysulfide inorganic glue is composed of the following components, by mass: 100 parts of light-burned magnesium oxide, 20-40 parts of magnesium sulfate heptahydrate, 60-85 parts of water, 4-15 parts of modifier and 3-5 parts of stabilizer.
[0010] Preferably, the modifier comprises: 1-3 parts of citric acid, 0.5-5 parts of silica fume, 0.3-2 parts of silica sol, 0.2-1 parts of lithium silicate, 0.3-1 parts of sodium tripolyphosphate and 0.5-3 parts of nano silicon.
[0011] Preferably, the stabilizer comprises: 1.5-3 parts of amphibole powder, 1-2 parts of sodium silicate and 0.3-0.5 parts of multi-walled carbon nanotubes.
[0012] In a second aspect, the present invention provides a method for preparing the modified magnesium oxysulfide inorganic glue, comprising the following steps: dissolving magnesium sulfate heptahydrate in water to obtain a magnesium sulfate solution; Then, silica sol, lithium silicate, sodium silicate, citric acid, sodium tripolyphosphate, nano-silicon, hornblende powder and multi-walled carbon nanotubes are added to the magnesium sulfate aqueous solution in proportion, stirred and mixed, and then light-burned magnesium oxide and silica fume are added, mixed and stirred continuously. After the reaction is completed, a modified magnesium oxysulfide inorganic glue is obtained.
[0013] Since light-burned magnesium oxide reacts rapidly with magnesium sulfate heptahydrate, if the order of adding the components is not adjusted and a retarder is not added, the inorganic colloid will have a too short setting time and will be difficult to apply to practical projects. During the preparation of the present invention, light-burned magnesium oxide and magnesium sulfate heptahydrate need to be mixed in steps, and before the two are mixed, the magnesium sulfate heptahydrate and the retarding component are ensured to be evenly mixed. In addition, silica fume, as a modifier, can improve the microstructure of the hydration product when light-burned magnesium oxide and magnesium sulfate heptahydrate react chemically, and further optimize the mechanical properties and structural stability of the colloid.
[0014] In a third aspect, the present invention provides a bamboo chip board, which is prepared by mixing the modified magnesium oxysulfide inorganic glue and bamboo chips in a mass ratio of 6-8:2-4.
[0015] In some embodiments, the method for preparing the bamboo chip board is as follows: bamboo chips generated during bamboo material processing and dead or dying bamboos are beaten into bamboo chips; After the bamboo chips are dried, they are mixed with the modified magnesium oxysulfide inorganic glue in a mass ratio of 2-4:6-8, and the mixture is poured into a mold, pressed into shape, and cured to obtain a bamboo chip board.
[0016] Preferably, the bamboo chips are sieving, and the diameter of the sieving bamboo chips does not exceed 2 mm, and the length does not exceed 10 mm.
[0017] Preferably, the moisture content of the bamboo chips after drying is less than 10%.
[0018] Preferably, the curing conditions are 20±3°C and relative humidity 60%RH.
[0019] More preferably, the curing time is 25-30 days.
[0020] The beneficial effects achieved by one or more embodiments of the present invention are as follows: Bamboo chip waste is compounded with modified magnesium oxysulfide inorganic glue to prepare modified magnesium oxysulfide inorganic glue bamboo chip board which does not contain harmful substances, has excellent mechanical properties, is fire-resistant and moisture-proof, has good durability, etc. It can be used in construction, furniture, decorative materials and other fields. It can reduce the energy consumption of building materials in the production stage, and can also fix carbon and reduce carbon dioxide emissions. It has both green and economic significance.
[0021] The modified magnesium oxysulfide inorganic glue prepared by the invention has a 28-day compressive strength of 63-95 MPa and a flexural strength of 7.5-15 MPa. The prepared modified magnesium oxysulfide inorganic glue bamboo chip board has a 28-day compressive strength of 34-55 MPa and a flexural strength of 12-18 MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0023] Figure 1 The diagram of the bending resistance test device of the modified magnesium oxysulfide inorganic glue (A) and the specimen failure diagram (B) in Example 1; Figure 2 The diagram of the compression test device of the modified magnesium oxysulfide inorganic glue (A) and the specimen failure diagram (B) in Example 1; Figure 3 This is a diagram of the compression test device in Example 2; Figure 4 It is a diagram of the compression test device in Comparative Example 1; Figure 5 The flexural test device diagram (A) and the specimen failure diagram (B) in Example 2; Figure 6 The flexural test device diagram (A) and the specimen failure diagram (B) in Comparative Example 1. DETAILED DESCRIPTION
[0024] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0025] The present invention will be further described below in conjunction with the embodiments.
[0026] In the following examples, bamboo chips were passed through a 10-mesh sieve and purchased from Zhuao (Shandong) Technology Co., Ltd.; Lightly calcined magnesium oxide with a MgO content of 98% to 99% was passed through a 400-mesh sieve and purchased from Wuxi Zemei New Material Technology Co., Ltd. Magnesium sulfate heptahydrate, purity above 95%, industrial grade, passed through 40 mesh sieve, purchased from Shandong Yongrui Salt Chemical Co., Ltd.; Silica fume, powder, passed through a 325-mesh sieve, purchased from Shijiazhuang Longcai Mineral Products Co., Ltd.; Silica sol, liquid, 30% content, purchased from Jinan Hongxinda Biotechnology Co., Ltd.; Lithium silicate, liquid, 25% content, purchased from Henan Youyang Chemical Products Co., Ltd.; Sodium silicate, powder, passed through a 325-mesh sieve, dissolved in water in advance, purchased from Luoyang Tongrun Information Technology Co., Ltd.; Citric acid, powder, dissolved in water in advance, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Sodium tripolyphosphate, powder, dissolved in water in advance, purchased from Sinopharm Chemical Reagent Co., Ltd.; Nano silicon, powder, dissolved in water in advance, Hubei Huifu Nanomaterials Co., Ltd.; Amphibole powder, powder, passed through a 300-mesh sieve, dissolved in water in advance, purchased from Fengfeng Mineral Products Processing Plant, Lingshou County; Multi-walled carbon nanotubes, purity above 85.5%, powder, sieved through 20,000 mesh, dissolved in water in advance, purchased from Jiaxing Bona New Materials Co., Ltd.
[0027] Example 1 A modified magnesium oxysulfide inorganic glue consists of the following components, measured by mass: 100 parts of light-burned magnesium oxide, 30 parts of magnesium sulfate heptahydrate, 80 parts of water, 0.8 parts of silica fume powder, 0.5 parts of silica sol, 1.0 parts of lithium silicate, 1.5 parts of sodium silicate, 1.5 parts of citric acid, 0.5 parts of sodium tripolyphosphate, 1.0 parts of nano silicon, 2.0 parts of amphibole powder and 0.3 parts of multi-walled carbon nanotubes.
[0028] Preparation method: Weigh each component according to the above material dosage ratio, dissolve magnesium sulfate heptahydrate in water and stir, and control the water temperature at 20° C. to obtain a magnesium sulfate aqueous solution; Then, silica sol, lithium silicate, sodium silicate, citric acid, sodium tripolyphosphate, 1.0 part of nano silicon, amphibole powder and multi-walled carbon nanotubes are added to the magnesium sulfate aqueous solution in sequence, and stirring is continued to ensure that all components are stirred evenly.
[0029] Finally, lightly burned magnesium oxide and silica fume are added and mixed and stirred until all components are fully reacted and uniformly to obtain modified magnesium oxysulfide inorganic glue.
[0030] Product performance: Test the compressive strength and flexural strength of inorganic glue The stirred modified magnesium oxysulfide inorganic glue was poured into a 40 mm x 40 mm x 160 mm mold to make 6 specimens, which were vibrated and compacted. The specimens were placed in a constant temperature (20±3°C) and constant humidity (relative humidity 60% RH) environment for 28 days, and the compressive strength and flexural strength of the modified magnesium oxysulfide inorganic glue were tested respectively.
[0031] Figure 1 The comparison of the modified magnesium oxysulfide inorganic glue before and after the flexural test of Example 1 is shown in FIG. Figure 1 Middle A and Figure 1 As shown in B, after testing, the 28-day flexural strength of the six specimens varied from 7.5 to 15 MPa, namely 7.53 MPa, 11.29 MPa, 13.84 MPa, 14.32 MPa, 14.73 MPa, and 15.28 MPa, with an average of 13.0 MPa.
[0032] Figure 2 The comparison of the modified magnesium oxysulfide inorganic glue before and after the compression test of Example 1 is shown in Figure 1. Figure 2 Middle A and Figure 2 As shown in B. In the compression test, the specimens (12 pieces) that were destroyed in the flexural test were used for the test. After testing, the 28-day compressive strength of the 12 specimens ranged from 63 to 95 MPa, namely 63.42 MPa, 66.44 MPa, 69.32 MPa, 73.46 MPa, 78.67 MPa, 80.97 MPa, 82.93 MPa, 85.36 MPa, 86.43 MPa, 87.95 MPa, 90.89 MPa, and 95.06 MPa, with an average of 79.24 MPa.
[0033] Example 2 A modified magnesium oxysulfide inorganic glue bamboo chip board consists of the following components, measured by mass: 30 parts of bamboo chips, 100 parts of light-burned magnesium oxide, 30 parts of magnesium sulfate heptahydrate, 80 parts of water, 0.8 parts of silica fume powder, 0.5 parts of silica sol, 1.0 parts of lithium silicate, 1.0 parts of nano silicon, 1.5 parts of sodium silicate, 1.5 parts of citric acid, 0.5 parts of sodium tripolyphosphate, 2.0 parts of amphibole powder and 0.3 parts of multi-walled carbon nanotubes.
[0034] Preparation method: Weigh each component according to the above material dosage ratio, dissolve magnesium sulfate heptahydrate in water and stir, and control the water temperature at 20° C. to obtain a magnesium sulfate aqueous solution; Then, silica sol, lithium silicate, sodium silicate, citric acid, nano-silicon, hornblende powder and multi-walled carbon nanotubes are added to the magnesium sulfate aqueous solution in sequence, and stirring is continued to ensure that all components are stirred evenly.
[0035] Finally, lightly burned magnesium oxide and silica fume are added and mixed and stirred until all components are fully reacted and uniformly to obtain modified magnesium oxysulfide inorganic glue.
[0036] Add the treated waste bamboo chips to the modified magnesium oxysulfide inorganic glue, stir evenly, and pour into a 40 mm x 40 mm x 160 mm mold for pressing. The formed bamboo chip board is cured in a constant temperature (20±3℃) and constant humidity (relative humidity 60% RH) environment for 28 days. The prepared modified magnesium oxysulfide inorganic glue bamboo chip board has a non-flammable grade of A1 and a formaldehyde emission of 0.
[0037] Comparative Example 1 Magnesium oxysulfide inorganic glue (authorization number CN 111423820B) bamboo chip board, calculated by mass, is composed of the following components: 30 parts of bamboo chips, 100 parts of light-burned magnesium oxide, 30 parts of magnesium sulfate heptahydrate, 60 parts of water, 0.8 parts of silica fume, 0.5 parts of silica sol, 1.0 parts of lithium silicate, 1.5 parts of sodium silicate and 1.5 parts of citric acid.
[0038] The preparation method is the same as that of Example 2, except that the component of the magnesium oxysulfide inorganic glue in Example 2 is changed.
[0039] Comparative Example 2 The difference from Example 2 is that nano silicon is replaced by silica ash, and the rest is the same as Example 2.
[0040] Comparative Example 3 The difference from Example 2 is that nano silicon is replaced by silica sol, and the rest is the same as Example 2.
[0041] Comparative Example 4 The difference from Example 2 is that sodium tripolyphosphate is replaced by nano silicon, and the rest is the same as Example 2.
[0042] Comparative Example 5 The difference from Example 2 is that sodium tripolyphosphate is replaced by citric acid, and the rest is the same as Example 2.
[0043] Comparative Example 6 The difference from Example 2 is that the amphibole powder is replaced with multi-walled carbon nanotubes, and the rest is the same as Example 2.
[0044] Comparative Example 7 The difference from Example 2 is that the multi-walled carbon nanotubes are replaced with sodium silicate, and the rest is the same as Example 2.
[0045] Referring to GB / T 17671-2021 "Test method for strength of cement mortar" (ISO method), compressive strength and flexural strength tests were carried out on 8 groups of inorganic glue bamboo chip board specimens in Example 2 and the comparative example.
[0046] Figure 3 This is a diagram of the compression test device in Example 2. Figure 5 It is the bending test device diagram (A) and the specimen failure diagram (B) in Example 2. The compressive strength of the bamboo chip board in Example 2 is 34-55 MPa, which are 34.32 MPa, 35.0 MPa, 35.53 MPa, 37.27 MPa, 38.10 MPa, 40.64 MPa, 42.76 MPa, 45.92 MPa, 48.81 MPa, 50.61 MPa, 52.38 MPa, 54.97 MPa, and the average is 43.03 MPa. The flexural strength is 12~18 MPa, which are 12.24 MPa, 12.76 MPa, 16.0 MPa, 16.53 MPa, 17.95 MPa, 18.32 MPa, and the average is 15.64 MPa; Figure 4 This is a diagram of the compression test device in Comparative Example 1, Figure 6 Figure 1 shows the flexural test device diagram (A) and specimen failure diagram (B) in comparative example 1. The compressive strength of comparative example 1 is 12-30 MPa, which are 12.43 MPa, 12.52 MPa, 13.96 MPa, 15.82 MPa, 17.71 MPa, 18.76 MPa, 20.45 MPa, 22.77 MPa, 24.51 MPa, 27.45 MPa, 28.82 MPa, and 30.42 MPa, with an average of 20.47 MPa. The flexural strength ranges from 4 to 10 MPa, namely 4.21 MPa, 6.75 MPa, 7.82 MPa, 8.56 MPa, 9.98 MPa and 10.34 MPa, with an average of 7.94 MPa. The compressive strength of Comparative Example 2 is 38-60 MPa, which are 38.25 MPa, 39.39 MPa, 39.62 MPa, 40.05 MPa, 43.72 MPa, 45.21 MPa, 46.06 MPa, 48.51 MPa, 50.81 MPa, 55.44 MPa, 58.76 MPa, and 60.16 MPa, respectively, with an average of 47.17 MPa; The flexural strength is 7~13 MPa, namely 7.12 MPa, 7.35 MPa, 8.97 MPa, 10.24 MPa, 12.75 MPa and 13.38 MPa, with an average of 9.97 MPa.
[0047] The compressive strength of Comparative Example 3 is 21-45 MPa, which are 21.44 MPa, 23.17 MPa, 26.58 MPa, 28.95 MPa, 33.62 MPa, 37.11 MPa, 39.52 MPa, 40.61 MPa, 42.88 MPa, 44.21 MPa, 44.74 MPa, and 45.39 MPa, with an average of 35.69 MPa; The flexural strength is 7.8~15 MPa, namely 7.88 MPa, 8.96 MPa, 10.54 MPa, 11.02 MPa, 13.43 MPa and 15.72 MPa, with an average of 11.26 MPa.
[0048] The compressive strength of Comparative Example 4 is 20-50 MPa, which are 20.52 MPa, 22.14 MPa, 26.96 MPa, 29.27 MPa, 35.94 MPa, 39.93 MPa, 41.81 MPa, 43.85 MPa, 44.01 MPa, 46.96 MPa, 48.75 MPa, and 50.17 MPa, respectively, with an average of 37.53 MPa; The flexural strength is 7~16 MPa, namely 7.20 MPa, 9.87 MPa, 11.06 MPa, 13.35 MPa, 14.98 MPa and 16.56 MPa, with an average of 12.17 MPa.
[0049] The compressive strength of Comparative Example 5 is 37-56 MPa, which are 37.58 MPa, 39.18 MPa, 40.99 MPa, 41.23 MPa, 42.08 MPa, 43.65 MPa, 45.3 MPa, 48.72 MPa, 52.06 MPa, 53.39 MPa, 55.47 MPa, and 56.26 MPa, respectively, with an average of 46.33 MPa; The flexural strength is 7~15 MPa, namely 7.53 MPa, 8.45 MPa, 11.76 MPa, 13.26 MPa, 14.94 MPa and 15.22 MPa, with an average of 11.86 MPa.
[0050] The compressive strength of Comparative Example 6 is 24-43 MPa, which are 24.23 MPa, 26.64 MPa, 28.98 MPa, 29.74 MPa, 32.62 MPa, 36.86 MPa, 38.05 MPa, 39.73 MPa, 41.21 MPa, 41.97 MPa, 42.31 MPa, and 43.08 MPa, respectively, with an average of 35.45 MPa; The flexural strength is 7~16 MPa, namely 7.26 MPa, 8.55 MPa, 10.94 MPa, 13.68 MPa, 15.13 MPa and 16.07 MPa, with an average of 11.94 MPa.
[0051] The compressive strength of Comparative Example 7 is 26-56 MPa, which are 26.46 MPa, 28.62 MPa, 29.31 MPa, 32.44 MPa, 35.73 MPa, 40.25 MPa, 41.25 MPa, 43.89 MPa, 46.93 MPa, 49.04 MPa, 51.22 MPa, and 52.67 MPa, respectively, with an average of 39.82 MPa; The flexural strength is 6~17 MPa, namely 6.13 MPa, 8.34 MPa, 10.69 MPa, 12.75 MPa, 15.42 MPa and 17.05 MPa, with an average of 11.73 MPa.
[0052] Table 1 Comparison of compressive strength and flexural strength between Example 2 and the comparative example
[0053] It can be found through experiments that the density and pore structure of the material are changed after the addition of bamboo chips, resulting in the compressive strength of the bamboo chip board being significantly lower than that of the rubber block. However, bamboo chips, as a natural fiber, significantly improve the toughness and flexural strength of the material. The experimental results of comparative example 2 and comparative example 1 show that the compressive strength and flexural strength of the modified magnesium oxysulfide inorganic glue bamboo chip board are significantly improved.
[0054] If the components of the modified magnesium oxysulfide inorganic glue are replaced, such as in Comparative Examples 2 and 3, nano silicon is replaced, through the test results of Comparative Examples 2, 3 and Example 2, it can be found that the addition of nano silicon plays an important role in the modified magnesium oxysulfide inorganic glue bamboo chip board, which not only improves the strength of the inorganic glue colloid, but also improves the bonding performance between the colloid and bamboo chips, and significantly improves the compressive strength and flexural strength of the bamboo chip board. This shows that nano silicon, as an effective modifier, has an advantage that is difficult to replace by other components (such as silica fume and silica sol) in enhancing the bonding between the colloid and bamboo chips.
[0055] Similarly, in Comparative Examples 4 to 7, sodium tripolyphosphate, hornblende powder and multi-walled carbon nanotubes were replaced respectively, and compared with the test results of the embodiment, it was found that the three ingredients of sodium tripolyphosphate, hornblende powder and multi-walled carbon nanotubes in the modified magnesium oxysulfide inorganic glue bamboo chip board play an important role in improving the strength of the colloid and the bonding performance between the colloid and bamboo chips.
[0056] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A modified magnesium oxysulfide inorganic glue, characterized in that: The invention is composed of the following components by weight: 100 parts of light-burned magnesium oxide, 20-60 parts of magnesium sulfate heptahydrate, 50-85 parts of water, 1.1-17 parts of a modifier and 1.8-5.3 parts of a stabilizer; The modifier comprises: 0.2-3 parts of citric acid, 0.5-8 parts of silica fume, 0.1-3 parts of silica sol, 0.2-2 parts of lithium silicate, 0.1-1 parts of sodium tripolyphosphate and 0.5-5 parts of nano silicon; The stabilizer comprises: 1-3.5 parts of amphibole powder, 0.5-3 parts of sodium silicate and 0.3-0.8 parts of multi-walled carbon nanotubes.
2. The modified magnesium oxysulfide inorganic glue according to claim 1, characterized in that: The invention is composed of the following components by mass: 100 parts of light-burned magnesium oxide, 20-40 parts of magnesium sulfate heptahydrate, 60-85 parts of water, 4-15 parts of a modifier and 3-5 parts of a stabilizer.
3. The modified magnesium oxysulfide inorganic glue according to claim 2, characterized in that: The modifier comprises: 1-3 parts of citric acid, 0.5-5 parts of silica fume, 0.3-2 parts of silica sol, 0.2-1 parts of lithium silicate, 0.3-1 parts of sodium tripolyphosphate and 0.5-3 parts of nano silicon.
4. The modified magnesium oxysulfide inorganic glue according to claim 2, characterized in that: The stabilizer comprises: 1.5-3 parts of amphibole powder, 1-2 parts of sodium silicate and 0.3-0.5 parts of multi-walled carbon nanotubes.
5. The method for preparing the modified magnesium oxysulfide inorganic glue according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: dissolving magnesium sulfate heptahydrate in water to obtain a magnesium sulfate solution; Then, silica sol, lithium silicate, sodium silicate, citric acid, sodium tripolyphosphate, nano silicon, amphibole powder and multi-walled carbon nanotubes are added to the magnesium sulfate aqueous solution in proportion, stirred and mixed, and then lightly burned magnesium oxide and silica fume are added and mixed. After the reaction is completed, a modified magnesium oxysulfide inorganic glue is obtained.
6. A bamboo chip board, characterized in that: The modified magnesium oxysulfide inorganic glue according to claims 1-4 is mixed with bamboo chips in a mass ratio of 6-8:2-4.
7. The bamboo chip board according to claim 6, characterized in that: The method for preparing the bamboo chip board comprises: beating bamboo chips generated in the bamboo material processing process and dead or dying bamboo into bamboo chips; After the bamboo chips are dried, they are mixed with the modified magnesium oxysulfide inorganic glue in a mass ratio of 2-4:6-8, and the mixture is poured into a mold, pressed into shape, and cured to obtain a bamboo chip board.
8. The bamboo chip board according to claim 7, characterized in that: The bamboo chips are processed by screening, and the diameter of the screened bamboo chips does not exceed 2 mm, and the length does not exceed 10 mm.
9. The bamboo chip board according to claim 7, characterized in that: The moisture content of the bamboo chips after drying is less than 10%.
10. The bamboo chip board according to claim 7, characterized in that: The curing conditions are 20±3°C and relative humidity is 60%RH; and the curing time is 25-30 days.
Citation Information
Patent Citations
Inorganic cemented soil modifier and application method thereof
CN104211315A
Magnesium oxysulfate fire door core board produced on rollout line
CN105503242A
Magnesium oxysulfate modifier
CN109665735A
Anti-cracking inorganic adhesive for bamboo structure, preparation method and preparation method of recombined bamboo
CN111393130A
Inorganic adhesive for bamboo-wood structures and preparation method thereof
CN111423820A
Cited By
Modified magnesium oxysulfate inorganic binder and preparation method therefor, and inorganic-bonded bamboo particle board
WO2026152795A1